2019
DOI: 10.1038/s41598-019-52481-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of endophytic fungi and screening of Huperzine A–producing fungus from Huperzia serrata in Vietnam

Abstract: Huperzine A (HupA), a natural Lycopodium alkaloid derived from Huperzia serrata (Thunb. ex Murray) Trev. plants, is a highly active acetylcholinesterase inhibitor and a key compound used for treating Alzheimer’s disease (AD). Recently, HupA has been reported in various endophytic fungi isolated from H. serrata. In the present study, 153 endophytic fungi were isolated from healthy tissues of H. serrata collected from natural populations in Lam Dong province of Central Vietnam. The endophytic fungi were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Currently, about 12 fungal genera have been reported to produce huperzine A [15][16][17][42][43][44][45][46][47], of which 7 genera were found in H. serrata in this study. Among them, Cladosporium, Trichoderma, and Fusarium with the relative abundance > 0.1% had the highest distribution in the stems, followed by the leaves and the roots, indicating that the endophytic fungi in the stems and the leaves were more involved in the synthesis of some secondary metabolites than those in the roots.…”
Section: Plos Onementioning
confidence: 60%
See 1 more Smart Citation
“…Currently, about 12 fungal genera have been reported to produce huperzine A [15][16][17][42][43][44][45][46][47], of which 7 genera were found in H. serrata in this study. Among them, Cladosporium, Trichoderma, and Fusarium with the relative abundance > 0.1% had the highest distribution in the stems, followed by the leaves and the roots, indicating that the endophytic fungi in the stems and the leaves were more involved in the synthesis of some secondary metabolites than those in the roots.…”
Section: Plos Onementioning
confidence: 60%
“…Previous studies examining the endophytic fungi of H. serrata and their secondary metabolic products revealed that they exhibited various biological activities, including antimicrobial activity, acetylcholinesterase inhibitory activity, nematocidal activity, and inhibition of nitric oxide production, among others [11][12][13][14]. In addition, some of endophytic fungi in H. serrata can produce huperzine A [15][16][17]. The distribution of some endophytic fungi in the host plants exhibited tissue specificity, which is an important influencing factor for accumulation of bioactive substances in different tissues [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The alkaloid drug Huperzine A (HupA) used to treat Alzheimer's disease is not only derived from the Huperzia serrata plant but also is produced and biosynthesized by the fungal endophyte Penicillium sp. LDL4.4 isolated from H. serrata [114]. In the legume Crotalaria (subfamily Fabaceae), the biosynthesis of pyrrolizidine alkaloids (antiherbivore, nematicide) depends on the nodulation by Bradyrhizobium sp.…”
Section: Endophytes Modulate Secondary Metabolites Of Medicinal Plantsmentioning
confidence: 99%
“…A suitable anti-biodegradable residue tissue block of 10 g was selected and washed with sterile normal saline three times, fungi were isolated by plant tissue separation ( Makhuvele et al, 2017 ; Thi Minh Le et al, 2019 ), the sample was repeated three times. Genomic DNA of the purified fungi was extracted using Ezup Column Fungal genomic DNA Extraction Kit (Qingke, Chongqing) and used as a template for internal transcribed spacer (ITS) region amplification ( Bellemain et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%